Сравнительная макро- и микроморфология мозжечка рыжей вечерницы и большого подковоноса - Омельковец, Я.А. (Вестник зоологии, 1993)
Locomotion and echolocation peculiarities are discussed as connected with macro- and micromorphology characters in examined bat species.